Selenium nanoparticle-enriched and potential probiotic, lactiplantibacillus plantarum S14 strain, a diet supplement beneficial for rainbow trout - Yáñez Lemus, Francisco.; Moraga, Rubén; Smith, Carlos T.; Aguayo Venegas, Paulina Andrea.; Sánchez Alonzo, Kimberly.; García Cancino, Apolinaria.; Valenzuela, Ariel; Campos, Víctor L. (MDPI, 2022)
Lactic acid bacteria (LAB), obtained from rainbow trout (Oncorhynchus mykiss) intestine, were cultured in MRS medium and probiotic candidates. Concurrently, producers of elemental selenium nanoparticles (Se0Nps) were selected. Probiotic candidates were subjected to morphological characterization and the following tests: antibacterial activity, antibiotic susceptibility, hemolytic activity, catalase, hydrophobicity, viability at low pH, and tolerance to bile salts. Two LAB strains (S4 and S14) satisfied the characteristics of potential probiotics, but only strain S14 reduced selenite to biosynthesize Se0Nps. S14 strain was identified, by 16S rDNA analysis, as Lactiplantibacillus plantarum. Electron microscopy showed Se0Nps on the surface of S14 cells. Rainbow trout diet was supplemented (108 CFU g−1 feed) with Se0Nps-enriched L. plantarum S14 (LABS14-Se0Nps) or L. plantarum S14 alone (LABS14) for 30 days. At days 0, 15, and 30, samples (blood, liver, and dorsal muscle) were obtained from both groups, plus controls lacking diet supplementation. Fish receiving LABS14-Se0Nps for 30 days improved respiratory burst and plasmatic lysozyme, (innate immune response) and glutathione peroxidase (GPX) (oxidative status) activities and productive parameters when compared to controls. The same parameters also improved when compared to fish receiving LABS14, but significant only for plasmatic and muscle GPX. Therefore, Se0Nps-enriched L. plantarum S14 may be a promising alternative for rainbow trout nutritional supplementation.
Keywords: Lysozyme; Nutritional supplement; Oncorhynchus mykiss; Production parameters; ROS; Selenium nanoparticles; Trucha arco iris; Estrés oxidativo; Probióticos